Do we need different protocols to support group-oriented cryptosystem? - Gumel, Lawan Ahmed; Leow, Soo Kar; Ramani, Ashwani Kumar (Faculty of Computer Science and Information Technology, University of Malaya, 1999)
Introduces some of the commonly known methods (protocols) used in key sharing/distribution problems, and finally shows that the existing protocols can be extended to support Group-Oriented Cryptoscheme (GOC). It is both a tutorial and an introduction to GOC.